Mechanized production of Kheer - Chauhan, Istiyakhusen Anavarhusen (Indian Journal of Dairy Science, 2017)
Kheer is a partially heat desiccated cereal-based sweetened, indigenous dairy dessert. It is considered nutritious as it is a rich source of protein, minerals, vitamins and other nutrients.Â Kheer occupies an important place in the list of delicacies liked by Indian population. As the systematic work on the development of suitable equipment for the mechanized production of such product was not reported, the study was planned to develop a SSHE and to evaluate its performance in terms of quality attributes of the products. The objectives of the study were to develop a SSHE suitable for the mechanization of Kheer and to evaluate the performance of the machine under different operating conditions. The study includes development of horizontal scraped surface heat exchanger (SSHE), its components and performance evaluation of the machine. The steam was used as a source of thermal energy required in manufacture of products. The performance of the machine was evaluated at steam pressure of 1.0, 1.5 and 2.0 kg/cm2, at scraper speeds of 10, 20 and 30 rpm and three levels of batch size viz., 10, 15 and 20 kg during kheer making. The quality of the product prepared under different operating conditions was evaluated for sensory attributes. The quality of the kheer prepared in SSHE under the operating conditions 1.0 kg/cm2 steam pressure, 30 rpm scrapper speed and 20 kg batch size was found superior in terms of the sensory attributes as compared to the products prepared at other operating conditions of the SSHE.